Applying tradable permits to biodiversity conservation: A conceptual analysis of trading rules - Silvia Wissel; Frank Wätzold (Helmholtz-Zentrum für Umweltforschung (UFZ), 2008)
Tradable permits have already been applied in many areas of environmental policy and may be a possible response to increasing calls for flexible conservation instruments which are able to successfully conserve biodiversity while allowing for economic development. The idea behind applying tradable permits to conservation is that developers wishing to turn land to economic purposes, thereby destroying valuable habitat, may only do so if they submit a permit to the conservation agency showing that habitat of at least the equivalent ecological value is restored elsewhere. The developer himself does not need to carry out the restoration, but may buy a permit from a third party thus allowing a market to emerge. However, applying tradable permits to biodiversity conservation is a complex issue, because destroyed and restored habitats are likely to differ. The purpose of this essay is to discuss on a conceptual level the consequences of these differences along the dimensions of type, space and time for the design of trading rules. We consider the resulting effects on trading activity in the permit market and the cost-effectiveness as well as the ecological effectiveness of the scheme. We find various trade-offs with regard to market activity, cost-effectiveness, ecological effectiveness and transaction costs .
Keywords: 330; Tradable permits; conservation policy; cost-effectiveness; habitat banking; economic development; land use; market based instruments; Biodiversität; Emissionsrechte; Naturschutz; Kosten-Wirksamkeits-Analyse